Target costing implementation in Malaysian automotive industry: an exploratory study / Hussein H. Hamood, Normah Omar and Suzana Sulaiman - Hamood, Hussein H.; Omar, Normah; Sulaiman, Suzana (Universiti Teknologi MARA, 2013)
Increasing competition coupled with changes of customers’ expectations has led many automotive companies to constantly upgrade its management accounting practices such as Target Costing (TC). This study aims to explore TC implementation in Malaysian automotive industry. Semistructured interview and site-visit approaches are employed by which the basic implementation stages of TC are explored. The results indicated some clear differences in the methods used to achieve TC by Malaysian automotive companies than the US and Japanese companies. The differences have been noted in determining selling prices and estimated costs as well as the less involvement of suppliers in the TC practices. The factors of intense competition, functional knowledge of employees and cooperation between departments has been found to be the most influential factors of TC implementation. The results have been ultimately used as a constructive validity method to enhance knowledge on the topic of interest and develop the questionnaire survey for future research.